Germline Single-Nucleotide Polymorphism GFI1-36N Causes Alterations in Mitochondrial Metabolism and Leads to Increased ROS-Mediated DNA Damage in a Murine Model of Human Acute Myeloid Leukemia - Jan Vorwerk; Longlong Liu; Theresa Helene Stadler; Daria Frank; Helal Mohammed Mohammed Ahmed; Pradeep Kumar Patnana; Maxim Kebenko; Eva Dazert; Bertram Opalka; Nikolas von Bubnoff; Cyrus Khandanpour (Biomedicines)
Background/Objectives: GFI1-36N represents a single-nucleotide polymorphism (SNP) of the zinc finger protein Growth Factor Independence 1 (GFI1), in which the amino acid serine (S) is replaced by asparagine (N). The presence of the GFI1-36N gene variant is associated with a reduced DNA repair capacity favoring myeloid leukemogenesis and leads to an inferior prognosis of acute myeloid leukemia (AML) patients. However, the underlying reasons for the reduced DNA repair capacity in GFI1-36N leukemic cells are largely unknown. Since we have demonstrated that GFI1 plays an active role in metabolism, in this study, we investigated whether increased levels of reactive oxygen species (ROS) could contribute to the accumulation of genetic damage in GFI1-36N leukemic cells. Methods: We pursued this question in a murine model of human AML by knocking in human GFI1-36S or GFI1-36N variant constructs into the murine Gfi1 gene locus and retrovirally expressing MLL-AF9 to induce AML. Results: Following the isolation of leukemic bone marrow cells, we were able to show that the GFI1-36N SNP in our model is associated with enhanced oxidative phosphorylation (OXPHOS), increased ROS levels, and results in elevated γ-H2AX levels as a marker of DNA double-strand breaks (DSBs). The use of free radical scavengers such as N-acetylcysteine (NAC) and α-tocopherol (αT) reduced ROS-induced DNA damage, particularly in GFI1-36N leukemic cells. Conclusions: We demonstrated that the GFI1-36N variant is associated with extensive metabolic changes that contribute to the accumulation of genetic damage.